2022
DOI: 10.1007/s40262-022-01133-2
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Delamanid and its Main Metabolite DM-6705 in Drug-Resistant Tuberculosis Patients Receiving Delamanid Alone or Coadministered with Bedaquiline

Abstract: Background and Objective Delamanid is a nitroimidazole, a novel class of drug for treating tuberculosis, and is primarily metabolized by albumin into the metabolite DM-6705. The aims of this analysis were to develop a population pharmacokinetic (PK) model to characterize the concentration-time course of delamanid and DM-6705 in adults with drug-resistant tuberculosis and to explore a potential drug–drug interaction with bedaquiline when coadministered. Methods Delamanid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In addition, dysregulation of CD8 T cells, overactivation of mTORC1 signaling, and decreased levels of GSH, impair of autophagy and mitophagy processes which impact decreasing M.Tb microbial clearance in elderly. (Bonavida et al, 2022) Interestingly, the absorption of bedaquiline and delamanid was not affected by age, and concomitant use of delamanid with bedaquiline had no impact on the pharmacokinetic profile delamanid and its metabolite, DM-6705 (Tanneau et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, dysregulation of CD8 T cells, overactivation of mTORC1 signaling, and decreased levels of GSH, impair of autophagy and mitophagy processes which impact decreasing M.Tb microbial clearance in elderly. (Bonavida et al, 2022) Interestingly, the absorption of bedaquiline and delamanid was not affected by age, and concomitant use of delamanid with bedaquiline had no impact on the pharmacokinetic profile delamanid and its metabolite, DM-6705 (Tanneau et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…12 A mixed-effect pharmacokinetic modeling study reported that albumin concentrations, HIV coinfection, or bedaquiline coadministration did not have an effect on delamanid pharmacokinetics. 21 This is the first study assessing the plasma levels of bedaquiline and delamanid in a cohort of patients with pre-XDR TB in India. One limitation of the study is its small sample size that limits any conclusions regarding an association between drug exposure and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 12 A mixed-effect pharmacokinetic modeling study reported that albumin concentrations, HIV co-infection, or bedaquiline coadministration did not have an effect on delamanid pharmacokinetics. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Plasma albumin concentration had no discernible effect on delamanid metabolism. Delamanid PK was not affected by the co-administration of bedaquiline (Tanneau et al, 2022). Using a large body of delamanid clinical data, a PK model for delamanid was developed in individuals with pulmonary MDR-TB.…”
Section: Mechanisms and Pharmacokinetics Of Delamanidmentioning
confidence: 99%